Tax Revenue and Taxpayer Compliance Before and After the PPS: A Comparative Analysis - Ida Indriani; Sony Devano (LANCAH: Jurnal Inovasi dan Tren, 2026)
This study aims to analyze the effect of the Voluntary Disclosure Program (PPS) on tax revenue and taxpayer compliance at the Directorate General of Taxes Regional Office of West Java I during the period 2019–2022. The study uses secondary data on realized tax revenue and compliance in submitting Annual Tax Returns (SPT) across 17 tax service offices that possess complete datasets. The analysis was conducted using a descriptive trend approach and a paired sample t-test to compare conditions before and after the implementation of the PPS. The results indicate that the PPS significantly increased tax revenue, as reflected in the substantial rise in revenue in 2022. However, the program did not produce a significant change in the level of taxpayer compli-ance, which remained fluctuating throughout the observation period. These findings support the theoretical perspective that fiscal incentive based policies tend to be effective in increasing government revenue in the short term, but do not necessarily lead to sustained improvements in taxpayer compliance behavior. This study provides empirical evidence regarding the effectiveness of the PPS by highlighting the differences between its short-term and long-term impacts on two key taxation indicators, namely tax revenue and taxpayer compliance.